THE ROLE OF CHARACTER EDUCATION IN REDUCING THE RECIDIVISM RATE - Masni, Masni; Kamaruddin, Syamsu A; Asriadi, Muhammad (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2024)
This research explores the role of character education in reducing recidivism among former inmates, with a focus on the Class II Penitentiary in Polewali Mandar. The issue of recidivism reflects weaknesses in the rehabilitation and social reintegration of inmates, which can be addressed through character education. Character education aims to develop moral and ethical values, as well as the ability to adapt in new social environments, helping former inmates recognize and correct past mistakes. A qualitative method with a case study approach was used to collect data through in-depth interviews, participatory observation, and document analysis. The results show that inmates who participate in character education programs exhibit positive changes in behavior and a decrease in the recidivism rate by 20-30%. The implementation of this program was successful through collaboration between correctional institutions, government, and non-governmental organizations. This research concludes that character education plays a significant role in reducing recidivism and recommends enhancing instructor training, psychosocial support, ongoing monitoring, and community collaboration for the success of the program